The impacts of perceived organizational support and psychological empowerment on job performance: The mediating effects of organizational citizenship - Iraj Soltani; Rasool Sarihi Asfestani; Hamideh abbasi (مطالعات مدیریت بهبود و تحول, 2013)
As employees' deliberate and conscious behavior, organizational behavior has critical influence on their job performance. Hence, their psychological empowerment enables the organizations to have higher flexibility and faster responsiveness toward changes. At the same time, perceived organizational support implies the employees' perception of the value of their attempts, health, and well-being for the organization.Accordingly, with respect to the importance of these factors in the organizations, the present study examines the effect of the relationship between organizational support and psychological empowerment on job performance with respect to the mediating role of organizational citizenship behavior. . The population of this research, finance and treasury staff supervision department of the Ministry of Economy and Finance, which have a total of 168 cases, the random method used and the population sample through Cochran formula, 117 were obtained. In order to collect survey data, standardized questionnaire and Tsvng Hai (2012) was used. Also, to increase the validity of the opinions of experts and specialists in this field has benefited from the Ministry of Economy and Finance. Using Cronbach's alpha (0.86) was used to determine reliability.In this analysis, the correlation matrix, regression, path analysis and structural equation modeling was performed using the statistical software LISREL. The findings indicate that perceived organizational support (0.11). And empowerment (0.12) alone does not affect job performance. However, OCB as an effective mediator between perceived organizational support (0.38) and psychological empowerment (0.59) with job performance. Organizations benefiting from the results, in the modern world that is constantly changing will be able to outdo the competition